2004
DOI: 10.1111/j.0958-7578.2004.00476.x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing red cell transfusion by audit, education and a new guideline in a large teaching hospital

Abstract: Safety concerns combined with the greatly increased costs and difficulties of maintaining the blood supply are major considerations for transfusion services. Previous local surveys demonstrated that hospital blood use at our hospital could be improved. Excessive cross-matching, unnecessary transfusion and high return rates of unused blood were commonplace. Transfusion practice was audited over a 3-month period. An education package with guidelines for transfusion was delivered to all clinician groups within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 9 publications
0
28
0
Order By: Relevance
“…Adequate education about appropriate blood use should target these later transfusions, which could potentially reduce the demand for blood; the effect of provider education on the use of blood has previously been highlighted. 12,18,19 Overall there appeared to be a low threshold for giving a red cell transfusion. It is appreciated that identifying symptoms of anaemia is difficult as such symptoms are often non-specific and highly subjective.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Adequate education about appropriate blood use should target these later transfusions, which could potentially reduce the demand for blood; the effect of provider education on the use of blood has previously been highlighted. 12,18,19 Overall there appeared to be a low threshold for giving a red cell transfusion. It is appreciated that identifying symptoms of anaemia is difficult as such symptoms are often non-specific and highly subjective.…”
Section: Discussionmentioning
confidence: 97%
“…12,18,19 This retrospective study preceded the publication of the RCOG national guidelines on blood transfusion that are intended to be incorporated into a protocol for all obstetric units in the UK. It is hoped that future audits following the implementation of these guidelines in the obstetric department at the John Radcliffe Hospital will replicate the same success in reducing red cell transfusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Audits carried out before the initiative and after one year showed that red cell use had decreased by 20%, with no demonstrable effect on morbidity or mortality. 20 …”
Section: Intra-operativementioning
confidence: 99%
“…Although cardiovascular morbidity, mortality, and length of stay did not change, 20% fewer patients received blood and 19% fewer packed red blood cell (PRBC) units were transfused [54]. Another tertiary academic center inserted evidence-based decision support for RBC transfusion into the computerized physician order entry system.…”
Section: Guidelines and Targeted Therapymentioning
confidence: 99%